Problems and analysis of fiber link acceptance test on the user side - Jian LIU; Shaoxian CHEN (Dianxin kexue)
The related standards of fiber to the home engineering were introduced.The connection mode and transmission requirements of fiber link on the user side were described.According to the test experience accumulated in recent years,the problems and causes found in optical fiber link acceptance test were analyzed and the suggestions on how to guarantee the link quality were also put forward.